An Appraisal of Extension Service Delivery through Mobile Veterinary Units (MVUs) in Odisha (Indian Journal of Extension Education, 2019)
An ingenious way of livestock service delivery at farmers’ doorstep through Mobile Veterinary Units (MVUs) under Rastriya Krishi Vikas Yojana (RKVY) is operational in all the 314 blocks of Odisha, with one of the objectives being to educate people on scientific livestock farming technologies. The study was conducted with a sample size of 90 farmers and 23 veterinary service providers viz., Veterinary Surgeons (VSs) and Livestock Inspectors (LIs) to analyze the efficacy of extension service delivery by MVUs and farmers’ demand for livestock extension activities. The study concluded that, MVU professionals were very often associated with activities viz., awareness camp and home visit. Besides these, supply driven activities, input supply and training programmes for better animal husbandry were the most needed activities by the farmers. The service providers expressed that lack of time for extension activities and unawareness of farmers about importance of extension activities, were the major problems they faced while performing extension activities.